The Periodontal Health Awareness Level of Dental Students At Universitas Sumatera Utara – A Survey - Amalia, Martina (Indonesian Journal of Medical Anthropology, 2025)
As a future oral health professional, I should know that good oral hygiene habits and attitudes have an impact on more than just my own dental and oral health. They may nevertheless have an impact on a patient's capacity to inspire them to take preventative action. A crucial and integral component of overall health is oral health. In comparison to professionals who see the dentist more regularly (43%), students visit the dentist for routine dental cleanings just about one-third as often as professionals. Describe periodontal health awareness levels among the Universitas Sumatera Utara dental students. This study uses a descriptive method (survey) using an adapted questionnaire. The sample was taken two times: the first stage (pilot study) required to test the validity and reliability of the questionnaire, and the second stage research on the periodontal health awareness level with 169 respondents. The questionnaire questions were valid and reliable. The results showed that for students who had an awareness of periodontal health levels in maintaining periodontal health, dental and oral health, the good were 97 respondents (57.4%), fairly good were 69 respondents (40.83%), less good was 3 respondents (1.78%). Most respondents of dental students at Universitas Sumatera Utara had a level of awareness of maintaining periodontal health in the good.